Pengaruh Terpaan Berita Mengenai Isu Rangka Smart Architecture Frame (eSAF) milik PT Astra Honda Motor Yang Mudah Patah dan Brand Image di Twitter Terhadap Tingkat Kepercayaan Konsumen Mengenai Kualitas Motor PT Astra Honda Motor - Gibran, Alvien; Lukmantoro, Triyono; Suryanto Gono, Joyo Nur (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
In this era, technology has become one of the most advanced innovations in making daily activities easier. With a world that is always moving, there is always room for technology to develop in all aspects, one of which is transportation. Because motorbikes offer a variety of flexible and affordable price options compared to other transportation methods, motorbikes have become one of the most popular methods of transportation and are the people's choice. The number of people who own motorbikes is increasing every month due to the fact that motorbikes are a practical way of transportation. In this process, a problem arose that the PT Astra Honda Motor eSAF frame became rusty and broke easily. This is very disappointing for customers because PT Astra Honda Motor is committed to providing the best products and quality. However, this fact shows that the promised product and quality failed to meet expectations, which of course harmed PT Astra Honda Motor's customers. The theories used in this research are New Media Theory and also e-WOM (Word of Mouth) Theory, with a sampling technique in the form of non-probability sampling, with a total sample of 100 people with characteristics of men and women, aged 16-64 years, and who had been exposed to news about the issue of PT Astra Honda Motor's eSAF frame being rusty and breaks easily. The results of hypothesis testing using a simple linear regression technique show that there is an influence between exposure to news about PT Astra Honda Motor's eSAF frame which rusts and breaks easily and brand image on Twitter on the level of consumer confidence regarding the quality of PT Astra Honda Motor's motorbikes with significance values in both hypotheses. of 0.000.